Perceived oral hygiene habits amongst 16-year-old school children - Mohd Sham, Shaharuddin; Yusoff, Mohd Kamil; Yaziz, Muhammad Ismail; Ramli, Mohamad Firuz; Abdullah, Mohd Yunus (2009)
This study was aimed at assessing dental habits among 16-year-old schoolchildren A total of 116 16-year-old schoolchildren took part in this survey, which was part of a larger study to assess dental fluorosis occurrence among the respondents. A questionnaire was given to each respondent prior to getting written consent from the parents. They were asked three categories of questions pertaining to habits of oral hygiene, firstly the number of tooth-brushings per day, then the quantity of toothpaste used per brushing, and lastly the number of visits to the dentist per year. From 116 respondents, 32 (27.6%) were males and 84 (72.4%) were females. On the first question, 100 respondents (86.2%) used fluoridated toothpastes while the remaining 16 (13.8%) used non-fluoridated toothpastes For the second question, 8 respondents (6.8%) brushed their teeth once per day, 59 (51.0%) twice per day, 35 (30.1%) three times per day and 14 (12.1%) 4 times per day About the question on quantity of toothpaste used for brushing (question 3), 25 respondents (21.5%) used ½ pea size, 66 (56.8%) used 1 pea-size, 24 (20.9%) used 2 pea-size and 1 (0.8%) used 3 pea-size. For the final question (question 4), 43 (37.1%) had never had any dental visits all their life, 33 (28.4%) had one dental visit per year, 30 (25.9%) had twice-a-year visit, 4 (3.4%) had 3 visit, 3 (2.6%) had 4 times-a-year visit and 3 (2.6%) had more than 4 times-a-year visit. This study concluded that more oral health education programs should be organized to improve the understanding of oral hygiene and the importance of dental visits in order to sustain a healthy oral life for a lifetime especially for the respondents.